PELATIHAN OPTIMALISASI MEDIA SOSIAL UNTUK PENINGKATAN BRANDING DAN PENJUALAN BAGI PELAKU UMKM DI DESA SELOKATON, GONDANGREJO, KARANGANYAR - Hakim, Luqman; Abbas, Ngatmin; Musthofa, Abdul Aziz; Yusuf, Muhammad; Amin, Nasihul; Pujiana, P; Sari, Yuliana; Irawan, Muh Heri (AL HAZIQ: Journal of Community Service, 2025)
Social media is an effective marketing tool yet to be optimally utilized by UMKM in Selokaton Village. Challenges faced include limited understanding of digital marketing, digital content creation skills, and limited training access. This program aims to enhance digital literacy, technical skills in creating digital content, and social media management. Implementation methods included theoretical training and direct practice covering digital branding basics, introduction to social media features, and practical simulations. Results showed increased participant understanding of digital branding and enhanced content creation skills. Participants effectively managed their social media professionally, boosted customer interaction, and strengthened brand awareness. In conclusion, this program significantly enhanced the digital marketing capabilities of UMKM in Selokaton Village.